Intraarterial thrombolysis with r-tPA for treatment of anterior circulation acute ischemic stroke: Technical and clinical results - (:unkn) unknown (My University, 2003)
To investigate factors effecting the safety and recanalization efficacy of local intraarterial (IA) recombinant tissue plasminogen activator (r-tPA) delivery in patients with acute ischemic stroke. Eleven patients with anterior circulation acute ischemic stroke were treated. The neurological status of the patients were graded with the Glasgow Coma Scale (GCS) and National Institute of Health Stroke Scale (NIHSS). All patients underwent a computed tomography (CT) examination at admission. In addition four patients had diffusion-weighted and one patient had a perfusion magnetic resonance (MR) examinations. Patients were treated within six hours from stroke onset. Immediate, six hours, and 24 hours follow-up CT examinations were performed in order to evaluate the haemorrhagic complications and the extent of the ischemic area. The Rankin Scale (RS) was used as an outcome measure. Two of the 11 patients had carotid "T" occlusion (CTO), nine had middle cerebral artery (MCA) main trunk occlusion. Four patients had symptomatic haemorrhage with a large haematoma rupturing into the ventricles and subarachnoid space. Of these, three patients died within 24 hours. The remaining seven patients had asymptomatic haematomas that were smaller compared to symptomatic ones, and showed regression in size and density on follow-up CTs. At third month five patients had a good outcome and three patients had a poor outcome. In acute ischemic stroke, local IA thrombolysis is a feasible treatment when you select the right patient. Haemorrhage rate does not seem to exceed that occuring in the natural history of the disease and in other treatment modalities.
Keywords: Intraarterial thrombolysis; Ischemic stroke; r-tPA